1988
DOI: 10.1016/s0022-5347(17)41470-4
|View full text |Cite
|
Sign up to set email alerts
|

Ex Situ Study of the Effectiveness of Enucleation In Patients with Renal Cell Carcinoma

Abstract: We wished to identify the efficacy of enucleation (excavation) in the treatment of renal cell carcinoma. Surgical specimens from 26 patients with polar or peripheral lesions, 50 per cent of which were found incidentally by computerized tomography scan, were considered amenable to this form of treatment and were studied by ex situ enucleation after standard radical nephrectomy. Eleven patients were determined to have unsuccessful enucleation after histopathological study demonstrated capsular invasion, vascular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
1

Year Published

1991
1991
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(26 citation statements)
references
References 18 publications
1
24
0
1
Order By: Relevance
“…Then, from the early 1980s, concurrently with the renewed interest in conservative surgery, many reports evaluated PS and SM status either on an RN specimen or on the sole tumor, but after an ex vivo TE, to investigate the real need to remove a rim of healthy tissue around the tumor. These studies noted some degree of PS invasion with RCC, irrespective of tumor size and histologic subtype, with a higher rate in larger and less-differentiated tumors, and thus TE was not recommended because of the significant risk of incomplete excision, although none histologically analyzed the tumor removed during an in vivo TE [8][9][10]. Indeed, Rocca Rossetti et al noted a continuous PS in 80% of tumors of <7 cm in diameter; in larger tumors this fraction was only 23.5% [8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Then, from the early 1980s, concurrently with the renewed interest in conservative surgery, many reports evaluated PS and SM status either on an RN specimen or on the sole tumor, but after an ex vivo TE, to investigate the real need to remove a rim of healthy tissue around the tumor. These studies noted some degree of PS invasion with RCC, irrespective of tumor size and histologic subtype, with a higher rate in larger and less-differentiated tumors, and thus TE was not recommended because of the significant risk of incomplete excision, although none histologically analyzed the tumor removed during an in vivo TE [8][9][10]. Indeed, Rocca Rossetti et al noted a continuous PS in 80% of tumors of <7 cm in diameter; in larger tumors this fraction was only 23.5% [8].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, other retrospective analyses confirmed that TE can be safely used for treating pT1a-pT1b RCC tumors, and it is not associated with any greater risk of local recurrence than is partial nephrectomy [20][21][22][23]. Therefore, the discrepancy between the optimal oncologic results of in vivo TE reported in several recent retrospective analyses [20][21][22][23] and the pathologic concerns of incomplete tumor excision based on data obtained by studies after an ex vivo TE or tumor sections of RN specimens remains an unsolved oncologic issue in conservative kidney surgery [8,[9][10][11].…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Tumor enucleation has been shown to be effective in providing intermediate cancer-free intervals in patients with peripheral lesions (17,18). However, other authors reported increasing as compared with the partial nephrectomy incidence of local recurrences after simple enucleation (19,20). We think, this can be explained by the blunt finger enucleation technique instead of sharp dissection and improper patient selection.…”
Section: Commentsmentioning
confidence: 84%
“…This evidence may depend on an incomplete tumor dissection or on a multifocal renal tumor. Rosenthal et al [15] and Blackley et al [16] showed that the pseudocapsule of the tumor is not a uniform and homogenous structure, but presents many breaks and neoplastic infiltrations (fig. 3); therefore, tumor dissection must be performed at the distance of 5 mm around the neoplasm ( fig.…”
Section: Discussionmentioning
confidence: 99%